2014
DOI: 10.1136/neurintsurg-2014-011255.rep
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous closure of a dural arteriovenous fistula

Abstract: SUMMARYSpontaneous closure of a dural arteriovenous fistula (dAVF) is a rare condition and only a few cases have been reported since its first description in 1976. We report delayed and progressive spontaneous closure of a dAVF after massive intracerebral hemorrhage documented by angiographic studies before and after bleeding. To our knowledge, this is the first report to document gradual closure of a dAVF by serial angiographic studies. The mechanism of spontaneous closure of dAVFs has not been fully elucidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…All Cognard type III DAVFs were diagnosed following intracranial hemorrhage. Regarding literature review from published data of spontaneous closure of intracranial DAVFs by Al-Afif et al ,[12] this situation can occur in the fistulas classified as Cognard type I, IIa, IIa + b, IIb, III, and IV. The most common spontaneously resolving lesions were type I. Warren et al [39] reported another rare precipitating factor, i.e., spontaneous resolution of Cognard type IIa DAVF following spontaneous recanalization of the occluded sinus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All Cognard type III DAVFs were diagnosed following intracranial hemorrhage. Regarding literature review from published data of spontaneous closure of intracranial DAVFs by Al-Afif et al ,[12] this situation can occur in the fistulas classified as Cognard type I, IIa, IIa + b, IIb, III, and IV. The most common spontaneously resolving lesions were type I. Warren et al [39] reported another rare precipitating factor, i.e., spontaneous resolution of Cognard type IIa DAVF following spontaneous recanalization of the occluded sinus.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of spontaneous regression in cranial DAVFs with cortical venous reflux or higher type of Cognard classification is extremely rare. [1112]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several reports have described spontaneous closure of DAVF without any aggressive treatment. 1) 5) 12) On the other hand, a few cases of conversion to aggressive lesions have been reported, and one study reported that benign AVFs have a 2% potential for angiographically verified conversion. 18) Several theories have been suggested to explain the conversion of venous drainage pattern, including sinus thrombosis, change of sinus wall structure, and flow dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The DAVF closed completely 8 weeks after the hemorrhage. One year after the bleeding the patient was followed up, she was independent and had recovered but with mild aphasia and a slight hemiparesis on the right side [20].…”
Section: Casementioning
confidence: 99%